2017
DOI: 10.1071/aj16191
|View full text |Cite
|
Sign up to set email alerts
|

Integrated petroleum systems analysis to understand the source of fluids in the Browse Basin, Australia

Abstract: Abstract. The Browse Basin is located offshore on Australia's North West Shelf and is a proven hydrocarbon province, hosting gas with associated condensate in an area where oil reserves are typically small. The assessment of a basin's oil potential traditionally focuses on the presence or absence of oil-prone source rocks. However, light oil can be found in basins where source rocks are gas-prone and the primary hydrocarbon type is gas-condensate. Oil rims form whenever such fluids migrate into reservoirs at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Seismic mapping based on regional 2D and some 3D seismic survey data was tied to 60 key wells ( Figure 1) using a revised tectonostratigraphic framework ( Figure 2) for the basin. Recent seismic and well interpretations (Rollet et al, 2016a) are used to produce palaeogeographic maps ( Figure 3) and develop a regional 3D geological model of the Browse Basin (Palu et al, 2017). The model is used to map the gross thickness of each set of supersequences containing source rock facies; i.e.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seismic mapping based on regional 2D and some 3D seismic survey data was tied to 60 key wells ( Figure 1) using a revised tectonostratigraphic framework ( Figure 2) for the basin. Recent seismic and well interpretations (Rollet et al, 2016a) are used to produce palaeogeographic maps ( Figure 3) and develop a regional 3D geological model of the Browse Basin (Palu et al, 2017). The model is used to map the gross thickness of each set of supersequences containing source rock facies; i.e.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Integration of the palaeogeography with geochemical analyses has enabled a better understanding of the spatial and temporal distribution of the source rocks. The role of these Jurassic to earliest Cretaceous source rock pods is demonstrated in a petroleum systems model that aims to clarify the charge history of the basin and determine which active source kitchens may have generated the fluids in the known hydrocarbon accumulations (Palu et al, 2017).…”
Section: Figure1 Structural Elements Of the Browse Basin Andmentioning
confidence: 99%
See 2 more Smart Citations
“…In these data we found that prominent gas kick started in the Echuca Shoals Formation and/or the Darwin Formation. Although the Echuca Shoals Formation has a high Gamma Ray response, it is a source rock (Palu et al 2017). The observed prolific mud gases show that the unit is transmissive, thus we inferred that this unit could act as a thief zone for the purposes of exploration time scale fault seal analysis.…”
Section: Example Outcrop Mapping Of Fault Rockmentioning
confidence: 90%